2021
DOI: 10.1177/15910199211024056
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of intracranial aneurysms after flow diverter treatment including color-coded imaging (syngo iFlow) as a predictor of aneurysm occlusion

Abstract: Purpose Flow Diverters (FD) have immensely extended the treatment of cerebral aneurysms in the past years. Complete aneurysm occlusion is a process that often takes a certain amount of time and is usually difficult to predict. Our aim was to investigate different syngo iFlow parameters in order to predict aneurysm occlusion. Methods Between 2014 and 2018 patients with unruptured cerebral aneurysms treated with a FD were reviewed. Aneurysm occlusion and complication rates have been assessed. In addition, variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The literature shows that iFlow parameters can be applied in a variety of ways and clinical experience is still rare, especially when it comes to flow assessment after treatment with WEB devices. Compared with the data from Gölitz et al., we believe that the parameters used in this study are easier to apply, not only because they have already shown promising and successful in vivo 13 and clinical 14 results.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The literature shows that iFlow parameters can be applied in a variety of ways and clinical experience is still rare, especially when it comes to flow assessment after treatment with WEB devices. Compared with the data from Gölitz et al., we believe that the parameters used in this study are easier to apply, not only because they have already shown promising and successful in vivo 13 and clinical 14 results.…”
Section: Discussionmentioning
confidence: 76%
“…The reduction of intra-aneurysmal flow remains a central hypothesis for success after treatment with a WEB device and, to the best of our knowledge, has only been investigated once in literature using in vivo color-coded imaging (syngo iFlow). 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations